Wellbeing over 50: A capabilities approach - Paul Anand; Ranjeeta Thomas; Alastair Gray (The Open University, Economics Department, 2012)
Drawing on the three key relations in the capabilities approach (Sen, 1985) to welfare economics and using panel data from the English Longitudinal Survey of Aging, this paper illustrates how the capabilities approach to welfare economics can be used to understand wellbeing in older age. Specifically, we estimate models of variables related to all three aspects of a person's wellbeing: functionings, happiness and capabilities. Results indicate that the production of activities depends significantly inter alia on education, health and gender; that happiness depends on a wide variety of activities and that there are potentially significant gender inequalities in the constraints facing women compared with men. The paper concludes that the capabilities approach is a workable approach to empirical welfare economics, applicable to older age, and can generate a range of insights about welfare outcomes and their distribution.
Keywords: I31; 330; capabilities approach; happiness; functionings; constraints; heterogeneity; inequalities; older age